Clinical and Pathological Features in Horses With Advanced Arytenoid Chondritis. Issue 1 (January 2021) - Bolfa, Pompei; Cercone, Marta; Dennis, Michelle M.; Conan, Anne; Grevemeyer, Bernard; Ducharme, Norm G.
Equine arytenoid chondritis causes airway obstruction and abnormal upper airway noise due to a space-occupying lesion(s) and decreased abduction. Our objective was to compare clinical scores and ultrasonographic findings with gross and microscopic lesions of naturally occurring arytenoid chondritis, in order to guide surgical treatment. Seventeen naturally affected horses with advanced/severe chronic arytenoid chondritis and 4 control arytenoid cartilages were evaluated after partial arytenoidectomy. Cartilages were sectioned caudal to the corniculate process and the body of each arytenoid was measured. We assessed total gross area (TA), percentage of viable cartilage (VC), percentage of viable cartilage on the lateral wall, and medial expansion. Retrospectively, the gross lesions were used to suggest 2 preferred surgical management (SM) groups: those requiring partial arytenoidectomy and those amendable to focal medial resection (a conservative SM). TA of horses with arytenoid chondritis was significantly larger than controls ( P = .005), due to a layered lesion composed of cavitation, granulation tissue, fibrosis, inflammation, hemorrhage, and edema, with relatively equal medial and lateral expansion that distorted the geometry of the affected cartilage. The increased TA paralleled the presence of immature cartilage with disorganized primitive mesenchymal cells. TA and SM were positively correlated ( P = .01). All cases showed varying degrees of cartilage degeneration or necrosis, more severe medially; those appearing amenable to focal medial resection arytenoid group had significantly more viable cartilage on the lateral wall ( P = .02). The gross and histopathologic findings suggest a new surgical approach—focal medial resection—that may save the lateral wall of the arytenoid.